2009
DOI: 10.1097/aln.0b013e31819faa71
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Upper Airway Integrity by Residual Neuromuscular Blockade: Increased Airway Collapsibility and Blunted Genioglossus Muscle Activity in Response to Negative Pharyngeal Pressure

Abstract: Minimal neuromuscular blockade markedly increases upper airway closing pressure, partly by impairing the genioglossus muscle compensatory response. Increased airway collapsibility despite unaffected values for resting ventilation may predispose patients to postoperative respiratory complications, particularly during airway challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…To translate the observed findings to an increased airway stability, formal measurements of airway patency (upper airway closing pressure) are required. An increased upper airway closing pressure (to less negative values) has been demonstrated after neuromuscular blockade, partly due to an impaired response of the genioglossus muscle to negative pressure and is associated with a less stable airway 45 .…”
Section: Discussionmentioning
confidence: 99%
“…To translate the observed findings to an increased airway stability, formal measurements of airway patency (upper airway closing pressure) are required. An increased upper airway closing pressure (to less negative values) has been demonstrated after neuromuscular blockade, partly due to an impaired response of the genioglossus muscle to negative pressure and is associated with a less stable airway 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The lingering effects of NMBAs can thus have profound and potentially serious consequences on airway patency. Upper airway dilator muscles counter-act the negative intraluminal pressure generated by the respiratory pump muscles to maintain airway patency during inspiration [40, 41]. With residual paralysis however, the efficacy of these dilator muscles is markedly impaired, enough to significantly increase airway collapsibility [40, 41].…”
Section: Residual Paralysis and Outcomesmentioning
confidence: 99%
“…Upper airway dilator muscles counter-act the negative intraluminal pressure generated by the respiratory pump muscles to maintain airway patency during inspiration [40, 41]. With residual paralysis however, the efficacy of these dilator muscles is markedly impaired, enough to significantly increase airway collapsibility [40, 41]. By measuring pharyngeal and pulmonary function, we observed that upper airway obstruction occurs commonly during inspiration, even at minimal levels of neuromuscular block [40].…”
Section: Residual Paralysis and Outcomesmentioning
confidence: 99%
“…Postoperative residual curarization was also identified as one of the risk factors for upper airway obstruction, as it typically impaired the upper airway dilator muscle strength, while preserving inspiratory muscle function. [3738]…”
Section: Discussionmentioning
confidence: 99%